Avaliação ultra-sonográfica, perfil hormonal e imunoistoquímica de estrógeno e progesterona durante o ciclo estral em vacas Nelore(Bos taurus indicus) - Martin, Ian [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
Thirty Nelore cows were submitted to estrus synchronization using a single administration of lecirelina, at 25 mg dosage and seven days later, D+ Cloprostenol at, 0.15 mg being both administered intra-muscularly. The first 16 cows ovulating were selected and daily evaluation was performed by rectal palpation and ultrasound of the female reproductive tract followed by blood sampling. Endometrial samples were collected by biopsy at days 0, 5, 9, 13 and 19 of the estrous cycle to detect the presence of estrogen and progesterone receptors by immunohistochemistry. The cows were distributed in 3 groups: control (without endometrial sampling, n=8), D0 (sampling initiated at the day of ovulation, n=4) and D13 (sampling initiated at day 13 of the estrous cycle, n=4). The mean inter-estrus interval was 23.80 l 2.70. The progesterone plasma mean concentrations ranged from 0.06 ng/mL to 4.53 ng/mL, decreasing throughout the cycle and reaching the lowest value close to ovulation. The pattern was characterized by increasing values during the luteal phase. The estradiol 17-b mean concentrations ranged from 6.22 pg/mL to 14.10 pg/mL and these values did not change throughout the estrous cycle. The results obtained by the rectal palpation revealed that the uterine tone and thickness were changing throughout the estrous cycle, being elevated during the period close to ovulation, and they were decreased during the progesterone phase. The ultrasound demonstrates that the amount of fluid content on the cranial vaginal compartment and in the uterine horn lumen was modified throughout the cycle. The largest amount of fluid was observed during the closest period to estrus and small fluid accumulation was observed during the progesterone phase. However, cows that were submitted to endometrial sampling presented more fluid during the progesterone phase...
Keywords: Bovino - Reprodução; Ciclo estral; Imunoistoquímica; Receptores hormonais; Estrous cycle; Immunohistochemistry; Hormone receptors